Dynamic resource scheduling strategy for 5G network slicing based on improved greedy algorithm - Qiang CHEN; Caixia LIU; Lingshu LI (网络与信息安全学报)
Dealing with the problem of network resource utilization and the user experience,the network slicing as a novel technology is adopted in 5G.A dynamic resource scheduling strategy for 5G network slicing based on improved greedy algorithm was proposed.In the process of slice scheduling and user scheduling,a two layer slice-user model combined with the improved greedy algorithm was proposed,which ensured the slices with maximum service weight and the highest priority users combined together to complete corresponding services.The global resource optimal problem was transformed into a smaller sub problem by means of the optimal combination of each slice and every user,which improved the network resource utilization and the user experience in the meantime.The Matlab simulation results show that compared with existing algorithms,the proposed method could effective improve the system remaining resource utilization,system average QoE level and system throughput.